Workplace radiation dose monitoring in diagnostic radiography Centres of the Lake Zone Regions of Tanzania (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Occupational radiation doses in diagnostic radiography Centres of the Lake Zone Regions of Tanzania were measured and analyzed. Thermoluminiscent Dosimeters (TLDs) were distributed to 17 radiation workers from 8 selected medical centres over a period of three (3) months. The estimated ambient doses in the Centers was measured by using a calibrated survey meter RAM DA-3-2000 of TAEC under SSDL Laboratory. The individual dose recorded ranged from 0.09 to 1.12 mSv which were all below the ICRP limit of 5mSv for 3 months. The radiation dose (ambient) recorded at 1 m from the control lead glass window ranged from 2.15 µSv/h to 7.27 µSv/h. The ambient doses were compared to the limit of 7.5 µSv/h set by ICRP. Higher values of ambient doses and indivudual doses were observed in some centres which entails improper radiation safety and protection measures in radiation cantres. But with the use  of protective gears, radiation workers receive lower doses hence abide with ALARA principle.